PREPARATION AND EVALUATION OF GELLAN GUM-LINSEED GUM BLEND MICROBEADS FOR SUSTAINED RELEASE OF ACECLOFENAC - MAITY, SITANGSU; MAHAPATRA, SANTOSH KUMAR (International Journal of Applied Pharmaceutics, 2022)
Objective: The objective of the current investigation was to design aceclofenac encapsulated microbeads using gellan gum and linseed gum blends following ionotropic gelation by trivalent Al3+-ions as cross-linking agent. Methods: Various formulation parameters like polymer-polymer blend (gellan gum and linseed gum), proportion and concentration of aluminium chloride (i.e., cross-linker) were considered for preparation of different formulations. In vitro aceclofenac release from these microbeads was performed in 0.1 N HCl (pH 1.2) for a preliminary 2 h, and after this period, it was continued in phosphate buffer (pH 7.4) for the next 6 h (a total of 8 h). Results: These gellan gum-linseed gum microbeads of aceclofenac exhibited drug encapsulation efficiency of 27.70 ± 0.42 to 74.27±2.57 % and average sizes of gellan gum-linseed gum microbeads were ranged 739.57 ± 22.70 to 968.07 ± 42.24 µm. The release of drug (in vitro) from these gellan gum-linseed gum microbeads of aceclofenac demonstrated a sustained pattern of drug-releasing (over 8 h). Conclusion: These gellan gum-linseed gum microbeads can be used as an effectual option of polymeric carrier matrices for sustained release.